DESAIN CETAKAN INJEKSI PLASTIK PRODUK GANTUNGAN DINDING - Ardi Antariksa; Erdian Suntosa; Muhammad Yunus; Muhammad H Amrullah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Most people definitely need a tool or a place to hang an equipment at home, there are various types of hangers such as hangers with several links or units with various variants of shapes. The unit hanger product is the most interested in the conclusion of the author who conducted a survey in the Sungailiat sub-district market area, because the product is compact and easy to move and can also be used as a decoration in the house, but it becomes a problem when the double tip binding function of the product does not work properly. or you could say it's easy to detach because the condition of the walls of each house is different. After identifying, the product has dimensions that are not the same and relatively thick so that it can cause a sinkmark as in the product that the author identifies. Therefore, the author designs of the unit hanger product by utilizing and maximizing the Arbug 420C injection molding machine at the Bangka Belitung State Manufacturing Polytechnic by using the design steps from the book "Gastrow Injection Molds: 130 Proven Design 4Th" with the results of draft drawings, arrangement drawings , and working drawings. The author also analyzes the liquid flow using moldflow insight software with the help of a 3rd party PT. Reiken Quality Tools The results of the analysis are fill time of 5.275 seconds, Sinkmark of 5.367%, the position of the Air trap, Clamping force of 85 tons, and injection pressure of 69.89 Mpa as injection engine settings. Then after the design is done by selecting and considering each part and its function, we get a three plate mold with a slider where the cavity and core are inside the slider, a dispensing system without an ejector, using a pin point gate, a parabolic runner with a symmetrical layout